Dramatic Effect of Botulinum Toxin Type A on Hypertrophic Scar: A Promising Therapeutic Drug and Its Mechanism Through the SP-NK1R Pathway in Cutaneous Neurogenic Inflammation - Zhang, Shunuo; Li, Ke; Yu, Zhixi; Chai, Jun; Zhang, Zheng; Zhang, Yixin; Min, Peiru (Frontiers in Medicine, 2022)
Background: Hypertrophic scar formation may be related to cutaneous neurogenic inflammation (CNI) through the substance P-neurokinin 1 receptor (SP-NK1R) signaling pathway. As a widely used drug in aesthetic clinical work, botulinum toxin type A (BTX-A) has a therapeutic effect on scars, but the actual mechanism remains unclear. This study aimed to clarify the potential mechanism by which BTX-A inhibits CNI in hypertrophic scars both in vitro and in vivo. Methods: Tissue samples were obtained from surgical excisions. Immunohistological analysis was used to locate SP in human hypertrophic scars and normal skin. RT-PCR and western blot analysis were used to evaluate the expression of collagens after SP/BTX-A treatment. A rabbit ear scar model was used to explore the in vivo effect of BTX-A on scar treatment. Results: SP and NK-1R were overexpressed in hypertrophic scars compared to normal skin tissues. Collagen secretion of hypertrophic scar-derived fibroblasts increased with increasing doses of SP. However, BTX-A may downregulate collagen expression through SP-NK1R pathway with or without the presence of SP inducing agent capsaicin. Meanwhile, SP inhibited the expression of NK-1R, and this inhibition was blocked by pretreatment with BTX-A. In vivo, intralesional BTX-A injection can also reduce the volume of scars and inhibit collagen secretion. Capsaicin may cause more severe scar manifestations, while the therapeutic effect of BTX-A remains. Conclusion: Our research confirms that CNI stimulates fibroblasts during scar formation, while BTX-A can reduce collagen secretion by inhibiting the SP-NK1R signaling pathway, thus identifying a novel therapeutic target for this benign solid skin tumor.